Reading Painting as Visual Autobiography: Peranakan Paintings by Sylvia Lee Goh - Abdullah, Sarena (2015)
Sylvia Lee Goh had her first solo show in May 1998 at the Creative Center of the National Art Gallery, Kuala Lumpur in an exhibition entitled “Two Decades of Art from the Heart”. Having partaken in more than 50 exhibitions locally and abroad, Sylvia's works exemplify a captured and frozen moment in time of the Peranakan life and social legacy. The Peranakans, otherwise known as the Babas and Nyonyas, is a conspicuous group of acculturated Chinese in Malaya, particularly in the Straits Settlements (Penang, Malacca and Singapore) hence its other name, the Straits Chinese. For the last 30 years, Sylvia Lee Goh's paintings, as I deliberate in this paper capture and encapsulate her own memories and personal narratives in the form of her own visual autobiographical paintings.